Motor-Based Interventions in Children with Developmental Coordination Disorder: A Systematic Review and Meta-analysis of Randomised Controlled Trials - Jiaxin Gao; Yihan Yang; Xiaqing Xu; Dunbing Huang; Yangxin Wu; Hongfei Ren; Anren Zhang; Xiaohua Ke; Wei Song (Sports Medicine - Open)
Abstract Background Developmental coordination disorder (DCD) is a neuromotor disorder in children that is characterized by significant difficulties in fine and gross motor skills. The main interventions for children with DCD are motor-based interventions (MBI), and a large number of relevant randomized controlled trials (RCTs) have emerged in recent years, but the efficacy of different types of MBI on different outcome parameters is unclear. Therefore, the aim of this study was to assess the effectiveness of MBI on standardized motor tests, body functions, activity and participation performance, and psychosocial factors in children with DCD, and to explore the differential effects of different types of interventions (including process-oriented, task-oriented, or combined task- and process-oriented) on the above outcome parameters. Methods We conducted a systematic literature search of all studies published in PubMed, Web of Science, Embase, and the Cochrane Library up to January 31, 2024 to compile all RCTs on MBI for children with DCD. Participants in this study were children with DCD between the ages of 3 and 17, using standardised motor skills tests, body function, activity and participation performance, or psychosocial factors as study outcomes. We assessed the risk of bias for each study and the overall risk of bias using Cochrane's ‘risk of bias’ tool. Quantitative syntheses (meta-analyses) were conducted with effect sizes expressed as Hedges' g. Results A total of 32 studies were included in the meta-analysis. The results showed that MBI significantly improved the overall motor skills (g = 1.00, 95%CI [0.48,1.52], p < 0.001), balance function (g = 0.57, 95%CI [0.17,0.97], p = 0.005), cognitive function (g = 1.53, 95%CI [0.67,2.39], p = 0.001), muscle function (g = 0.91, 95%CI [0.17,1.66], p = 0.017), coordination function (g = 0.47, 95%CI [0.04,0.90], p = 0.032), visual function (g = 0.61, 95%CI [0.15,1.08], p = 0.009), sensory function (g = 0.85, 95%CI [0.34,1.35], p = 0.001), sensory organization function (g = 0.61, 95%CI [0.27,0.96], p = 0.001) and activity performance (g = 0.71, 95%CI [0.23,1.19], p = 0.004), but improvements in children's psychosocial factors (g = 0.71, 95%CI [− 0.08,1.50], p = 0.079) were not significant, nor were improvements in children's participation levels observed with MBI. Subgroup analyses further revealed that task-oriented training significantly improved overall motor skills, balance function, and activity performance in children with DCD, and that combined task- and process-oriented training also significantly improved overall motor skills in children with DCD. Conclusions MBI demonstrates significant positive effects on enhancing standardized motor test scores, body functions, and levels of activity performance in children with DCD. However, no improvements were observed in children's participation levels, and no statistically significant effects were observed on psychosocial outcomes. Our findings further highlight the comparative effectiveness of intervention strategies. Task-oriented approaches significantly improved overall motor skills, balance, cognitive function, and activity performance, while combined task- and process-oriented strategies also enhanced overall motor skills. In contrast, given the limited number of included studies, the effects of process-oriented strategies on motor skills and activity performance, as well as the impact of combined strategies on activity performance, remain inconclusive. In conclusion, our comprehensive study suggests the preference for employing task-oriented strategies or training underlying processes within task-oriented training for children with DCD. Registration The protocol of the investigation was registered in PROSPERO (ID: CRD42024499574). Key Points Motor-based interventions significantly improved standardized motor test scores, body functions, and activity performance levels in children with DCD, but no improvements were observed in participation levels or psychosocial outcomes. Task-oriented strategies were highly effective in improving motor skills, balance, cognitive function, and activity performance, while combined task- and process-oriented approaches also enhanced overall motor skills. The effects of process-oriented approaches on motor skills and activity performance, as well as the impact of combined strategies on activity performance, remain inconclusive due to the limited number of studies, emphasizing the need for further research.